An update of thin-toed gecko Tenuidactylus bogdanovi (Reptilia, Gekkonidae) population status in Odessa City, Ukraine - Krasylenko, Yu.А.; Kukushkin, O.V. (Збірник праць Зоологічного музею, 2017)
The new data regarding the current status of Bogdanov’s thin-toed gecko population in Odessa city are presented. A population density of lizards is relatively high. Fourteen individuals of T. bogdanovi (21.4 % of juveniles) were found at the “Moldavanka” historical district on an area of circa 3.75 hectares in late July — early August 2017. The positive dynamics of urban gecko’s population allows considering T. bogdanovi as naturalized adventive species — Turanian faunistic element in the fauna of Ukraine. The gecko’s population increase and steadily expands distributional area to several dozens of hectares, what was confirmed by indirect evidence. The scientific significance of only European population of T. bogdanovi is also highlighted. Photos of Bogdanov’s thin-toed gecko in its habitats in Odessa city are published for the first time.